تطبيق برنامج واتسآب في تعليم مهارة الكتابة لدى طلبة جامعة السلفية لعلوم الشريعة باميكاسان مادورا: Penerapan Aplikasi WhatsApp dalam Pengajaran Keterampilan Menulis Mahasiswa Universitas Salafiyah Ilmu Syari’ah Pamekasan Madura - Karim, Ahmad Fauzun; Aini, Cicik; Abd. Qadir, Ach. Mahfudz (Jiluna Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
With the onset of the Covid-19 pandemic, several changes occurred in aspects of human life. The process of education activity is not without the impact of this epidemic. The impact of the pandemic and its change in the education process, which usually took place automatically, is no exception. Recently, it has become virtual through social media such as WhatsApp and so on. Previous research confirmed that WhatsApp is more widely used. This research presents to readers a description of the application of the WhatsApp program in teaching writing skills to students at the Salafia University for Sharia Sciences, and its advantages and disadvantages, such as the researcher’s proposed solution to the problem of automatic learning throughout the Covid-19 pandemic. This research uses the type of qualitative research, the type of case study, and data collection methods with three of the following: Interview, observation and documentation. The method of analyzing it is by Mills and Hubbarman analysis. The results indicate that the application of the WhatsApp program in teaching writing skills during the Covid-19 pandemic occurs through three methods, which are pre-lecture, implementing the lecture, and evaluating the lecture. As for the advantages and disadvantages, one of its advantages is flexibility and its application is easier compared to other applications. The shortcomings include the lack of student equipment for all students and the limitation of other supportive means.